Phenotypic diversity and genotypic flexibility of Burkholderia cenocepacia during long-term chronic infection of cystic fibrosis lungs - Lee, Amy Huei-Yi; Flibotte, Stephane; Sinha, Sunita; Paiero, Adrianna; Ehrlich, Rachel L.; Balashov, Sergey; Ehrlich, Garth D.; Zlosnik, James E.A.; Mell, Joshua Chang; Nislow, Corey (Genome Research, 2017)
Chronic bacterial infections of the lung are the leading cause of morbidity and mortality in cystic fibrosis patients. Tracking bacterial evolution during chronic infections can provide insights into how host selection pressures—including immune responses and therapeutic interventions—shape bacterial genomes. We carried out genomic and phenotypic analyses of 215 serially collected Burkholderia cenocepacia isolates from 16 cystic fibrosis patients, spanning a period of 2–20 yr and a broad range of epidemic lineages. Systematic phenotypic tests identified longitudinal bacterial series that manifested progressive changes in liquid media growth, motility, biofilm formation, and acute insect virulence, but not in mucoidy. The results suggest that distinct lineages follow distinct evolutionary trajectories during lung infection. Pan-genome analysis identified 10,110 homologous gene clusters present only in a subset of strains, including genes restricted to different molecular types. Our phylogenetic analysis based on 2148 orthologous gene clusters from all isolates is consistent with patient-specific clades. This suggests that initial colonization of patients was likely by individual strains, followed by subsequent diversification. Evidence of clonal lineages shared by some patients was observed, suggesting inter-patient transmission. We observed recurrent gene losses in multiple independent longitudinal series, including complete loss of Chromosome III and deletions on other chromosomes. Recurrently observed loss-of-function mutations were associated with decreases in motility and biofilm formation. Together, our study provides the first comprehensive genome-phenome analyses of B. cenocepacia infection in cystic fibrosis lungs and serves as a valuable resource for understanding the genomic and phenotypic underpinnings of bacterial evolution.